Inverse association between carbohydrate consumption and plasma adropin concentrations in humans. Issue 8 (August 2016) - Stevens, Joseph R.; Kearney, Monica L.; St‐Onge, Marie‐Pierre; Stanhope, Kimber L.; Havel, Peter J.; Kanaley, Jill A.; Thyfault, John P.; Weiss, Edward P.; Butler, Andrew A.
Abstract : Objective: The role of metabolic condition and diet in regulating circulating levels of adropin, a peptide hormone linked to cardiometabolic control, is not well understood. In this study, weight loss and diet effects on plasma adropin concentrations were examined. Methods: This report includes data from (1) a weight loss trial, (2) an evaluation of acute exercise effects on mixed‐meal (60% kcal from carbohydrates) tolerance test responses, and (3) a meta‐analysis to determine normal fasting adropin concentrations. Results: Distribution of plasma adropin concentrations exhibited positive skew and kurtosis. The effect of weight loss on plasma adropin concentrations was dependent on baseline plasma adropin concentrations, with an inverse association between baseline and a decline in concentrations after weight loss (Spearman's ρ = −0.575; P < 0.001). When ranked by baseline plasma adropin concentrations, only values in the upper quartile declined with weight loss. Plasma adropin concentrations under the main area of the bell curve correlated negatively with habitual carbohydrate intake and plasma lipids. There was a negative correlation between baseline values and a transient decline in plasma adropin during the mixed‐meal tolerance test. Conclusions: Plasma adropin concentrations in humans are sensitive to dietary macronutrients, perhaps due to habitual consumption of carbohydrate‐rich diets suppressing circulating levels. Very high adropin levels may indicate cardiometabolic conditions sensitive to weight loss.